Developing a Summary Book of Arabic Grammar Rules With a Concept Map and Using It in Teaching Grammar: تطوير كتاب ملخص قواعد اللغة العربية بخريطة المفاهيم واستعمالها في تدريس النحو - Fajriah, Fajriah; Fira Mauliza; Musthafa, Jailani (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2025)
Based on observations made by researchers, students have difficulty in understanding nahwu learning by using the book mulakhas qawaid al-lughah al-'arabiyah without developing learning media such as concept maps. Therefore, researchers are interested in developing mulakhas qawaid al-lughah al-'arabiyah with concept maps, especially in the chapter of Inna and his brother. As for the objectives in this study: 1) to know the steps of developing kitab mulakhas qawaid al-lughah al-'arabiyah with concept maps in nahwu learning, 2) to know the validation of concept map media in nahwu learning. The research method used by researchers is the research and development method using Sugiyono's model. The steward used is an observation sheet. The results of this study are: 1) The steps of developing the book of mulakhas qawaid al-lughah al-'arabiyah with concept maps consist of analyzing needs and problems, collecting data, product design, product validation, and product revision. 2) Concept maps are feasible to use in learning after being assessed by experts. Expert results in terms of content and language are 95% (very feasible) and expert results in terms of design are 97,5% (very feasible).